Revolusi dan Inovasi Guru Pendidikan Agama Islam Sekolah Dasar - Makhasin Makhasin (Institut Agama Islam Negeri Purwokerto, 2016)
Abstract The development of the times in the global era is now demanding many changes. The revolution needed to be able to compensate the life in this global era. The teacher as an important component in the education system, it is natural to have a point of view that is advanced and flexible, accept the changes due to the development of the times. To face all the developments, both positive development, and negative development. Teacher should be able to do a self revolution that will affect the school environment in order to remain positive. Teacher have to evolve with innovations that is better, especially in bringing Islamic religious education in order to remain easy to be accepted in the global era now. Keywords : Revolution, Innovation, Teacher, and Islamic Religious Education. Abstrak Perkembangan jaman pada era global sekarang ini menuntut banyaknya perubahan. Revolusi diperlukan untuk dapat mengimbangi kehidupan di era global ini. Guru sebagai komponen penting dalam sistem pendidikan sudah sewajarnya memiliki sudut pandang yang maju dan fleksibel untuk dapat menerima perubahan sebagai dampak dari perkembangan jaman. Untuk menghadapi segala perkembangan yang tidak hanya berdampak positif, namun terdapat juga perkembangan ke arah negatif guru harus dapat melakukan revolusi diri yang akan mempengaruhi lingkungan sekolahnya agar tetap bernilai positif. Guru harus berkembang dengan inovasi-inovasi yang semakin lebih baik, khususnya dalam membawakan Pendidikan Agama Islam agar tetap mudah diterima pada era global sekarang. Kata kunci: Revolusi, Inovasi, Guru, dan Pendidikan Agama Islam.